Banquet and catering management - Rosalda, Francis Alvin; Vizconde, Angelie Marie L. (Sta. Cruz, Manila : Edric Publishing House, 2023)
Catering is the intended service for food and drinks according to the industry definition, as opposed to restaurants where food and drink are often on demand.
1. Historical Banqueting -- 2. Developing a catering business -- 3. Styles of catering operations -- 4. Catering Sales and marketing -- 5. Catering Menu program -- 6. Controls in operation -- 7. Catering menu, pricing and controls -- 8. Catering menu design -- 9. Catering beverage management -- 10. Quality-Serve and standards training -- 11. Managing Catering Equipment -- References.
Includes bibliographical references.
Keywords: CATERERS AND CATERING -- MANAGEMENT